On the theory of economic MPC: ELOC and approximate infinite horizon EMPC. (January 2019) - Adeodu, Oluwasanmi; Omell, Benjamin; Chmielewski, Donald J.
Highlights: Show that the EMPC phenomenon of inventory creep can occur within a reaction system. Show that EMPC performance degradation can occur abruptly with horizon size. Develop a novel infinite horizon framework for the EMPC problem. A framework to approximate the infinite horizon policy using dynamic programming. Advocate ELOC as the appropriate basis to approximate infinite horizon EMPC policy. Show that the approximate policy is insensitive to computational horizon size. Abstract: In recent years, the notion of Economic Model Predictive Control (EMPC) has gained significant interest. Despite a marked improvement in economic performance, it has been shown that this performance will degrade substantially if implemented with a horizon that is not sufficiently large. In the current effort, it is shown that if applied to a particular reaction process, EMPC performance will abruptly collapse at a critical horizon size. To alleviate this issue, we develop an Infinite Horizon EMPC (IH-EMPC) formulation. While this IH-EMPC problem is computationally intractable, it does lead to an approximation of the optimal policy. The resulting Approximate IH-EMPC (AIH-EMPC) is identical to the original finite horizon EMPC, but includes a final cost term that represents the objective function from the finite horizon to infinity. With two example systems, a chemical reactor and a power system with energy storage, it is shown that the AIH-EMPC policy is virtually insensitive to its computational horizon size.